2020
DOI: 10.1021/acs.jpcb.0c07263
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Molecular Mechanisms of Thickness-Dependent Water Dynamics in an Ultrathin Free-Standing Polyamide Membrane

Abstract: Aromatic polyamide (PA) membranes fabricated from interfacial polymerization are widely used for desalination and water treatment. The fabrication of the high-flux PA membrane requires a fundamental understanding of the molecular mechanisms of water dynamics in the PA, which is still obscure due to the limited experimental methods. Herein, molecular dynamics (MD) simulations were employed to establish an atomic model of ultrathin free-standing PA membranes with various thickness and to explore the thickness-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Overall, the analysis using the hindered transport model shows that the experimental R r −J w trends as the membranes become more permeable can be explained by a slight increase in d p and a substantial decrease in L. Because the marginal enlargement of the free volume sizes alone is not able to fully account for the markedly enhanced water permeabilities, the membrane structural property L is identified as a more significant factor governing A: shortening the effective transport pathway of the selective layer substantially elevates the membrane water permeability. This is consistent with the related studies that employed computational simulations and experimental characterizations of layer-by-layer polyamide membranes to show that water permeability is significantly influenced by the membrane thickness, 79,80 suggesting that L can be decreased by tuning the constituent elements, specifically thickness, fractional free volume, and tortuosity.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…Overall, the analysis using the hindered transport model shows that the experimental R r −J w trends as the membranes become more permeable can be explained by a slight increase in d p and a substantial decrease in L. Because the marginal enlargement of the free volume sizes alone is not able to fully account for the markedly enhanced water permeabilities, the membrane structural property L is identified as a more significant factor governing A: shortening the effective transport pathway of the selective layer substantially elevates the membrane water permeability. This is consistent with the related studies that employed computational simulations and experimental characterizations of layer-by-layer polyamide membranes to show that water permeability is significantly influenced by the membrane thickness, 79,80 suggesting that L can be decreased by tuning the constituent elements, specifically thickness, fractional free volume, and tortuosity.…”
Section: ■ Results and Discussionsupporting
confidence: 91%
“…A cross-linked PA molecule was created using 12 PIP and eight TMC molecules based on energy minimization . Next, the PA molecules, TA molecules, and Fe 3+ were originally placed inside a simulation box of 8.5 × 8.5 × 6 nm 3 , followed by amplification in the canonical ensemble (NVT) at 300 K and the homogenization via six heating–annealing cycles . The resulting cross-linked pristine network was solvated to mimic the swelling of the network in an alkaline solution.…”
Section: Methodsmentioning
confidence: 99%
“…36 Next, the PA molecules, TA molecules, and Fe 3+ were originally placed inside a simulation box of 8.5 × 8.5 × 6 nm 3 , followed by amplification in the canonical ensemble (NVT) at 300 K and the homogenization via six heating− annealing cycles. 37 The resulting cross-linked pristine network was solvated to mimic the swelling of the network in an alkaline solution. Alkaline solution with or without PEI molecules was first equilibrated at the normal pressure (NPT, 298.15 K, 1 bar) in an orthogonal box of 4 nm for 2 ns to obtain a suitable density of small cells.…”
Section: Molecular Simulationmentioning
confidence: 99%
“…28 Shi et al studied the swelling behavior of PA membranes and discussed the thickness-dependent dynamics behavior of water molecules. 29,30 Moreover, the nonequilibrium molecular dynamics (NEMD) simulations were performed to study the water transport process. For example, Gao et al studied the effects of pressure on the transport behavior of water molecules and found that the pressure accelerated the transport of water molecules.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In MD simulation, the construction methods of the PA model are similar to our former work, as shown in Figure 1. 29,30 The point charge (Mulliken charge) of piperazine (PIP) and 1,3,5-benzenetricarbonyl trichloride (TMC) molecules were calculated using B3LYP functional and the 6-31+g(d,p) basis set in the density functional theory calculations by the Gaussian 09 code. 32−34 After that, the structural parameters of all molecules, such as atom type, bond length, bond angles, and dihedral angles, were represented by the GROMOS force field and PRODRG.…”
Section: ■ Introductionmentioning
confidence: 99%